Presence of residual material following mini-hemilaminectomy in dogs with thoracolumbar intervertebral disc extrusion - Huska, Jonathan L. (Canadian Veterinary Medical Association, 2014)
Presence of residual material following mini-hemilaminectomy in dogs (n = 9) with spontaneous thoracolumbar intervertebral disc extrusion was prospectively investigated. Volume of extruded disc material within the vertebral canal and the proportion of residual material were determined using pre- and post-operative magnetic resonance imaging. The degree of spinal cord compression, proportion of extradural material considered hemorrhage, and invasion of the articular facets were also determined. Residual material was identified in 44% of the mini-hemilaminectomies. The median percentage of residual material calculated was 7.7% of the preoperative volume. No observed effect of surgical side or site, proportion of extradural material considered hemorrhage, patient weight, and duration of clinical signs was detected.